Maturation curve of jaboticaba ‘Sabará’ (Research, Society and Development, 2020)
Knowing the stages of fruit development is essential to determine cultural management practices and to know the commercial harvesting point of the fruits. However, the objective of this work is to study the evolution of the development processes of jaboticaba, still linked to the cultivated plant in the city of Piracicaba-SP. For this, 10 jaboticaba tree were selected from August to October 2016 and 2017. Ten fruits of each plant were measured with a pachymeter, totaling 100 fruits, to determine the longitudinal and transverse diameters during maturation, every five days. Fifty fruits were also collected for physical-chemical analysis of color, mean mass, total soluble solids content (SST) and titratable total acidity (ATT) during the development to compose the curve of fruit maturation, which were evaluated every five days. The data were submitted to analysis of variance to compare the two harvests evaluated and also to compare the different evaluated periods. The parameters that presented significant difference were adjusted to the regression equation and for the significant parameters that did not fit the regression, the Tukey test was performed at 5% of probability. The transverse diameter of the fruits was higher in the 2016 harvest when compared to the 2017 harvest, and for the other evaluated parameters there was no significant difference between the harvests. Changes in fruit diameters occurred until the end of the evaluated period and adjusted to an increasing linear model, however, maximum average mass gain was adjusted to the quadratic polynomial model, presenting maximum value at 35 days after the anthesis, stabilizing the from then on. The total soluble solids content and the titratable total acidity were adjusted to the linear model from increasing to first and decreasing to second. Increase in the ratio values (SST/ATT) along the development of the fruits suggests the best time to harvest them. The change in the color of the bark occurs 30 days after the anthesis and is not a good indicator of harvest point. Under the conditions of the study, 'Sabará' jaboticabas, harvested 45 days after anthesis have ideal quality both for the fresh fruit market and for processing.